2022
DOI: 10.3389/fpubh.2022.963673
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of COVID-19 pandemic on healthcare workers

Abstract: BackgroundAs unprecedented and prolonged crisis, healthcare workers (HCWs) are at high risk of developing psychological disorders. We investigated the psychological impact of COVID-19 pandemic on HCWs.MethodsThis cross-sectional study randomly recruited 439 HCWs in Hunan Cancer Hospital via a web-based sampling method from June 1st 2021 to March 31st 2022. Anxiety and depression levels were measured using Hospital Anxiety and Depression Scale (HADS). The Post Traumatic Stress Disorder (PTSD) Checklist for DSM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The prevalence rates of depressive and anxiety symptoms for healthcare workers in the post-pandemic era were generally comparable to those observed in previous studies during the COVID-19 pandemic era, but different from the prevalence before the pandemic. In this study, we found that the prevalence of depressive symptoms was 34.7%, which was nearly in line with that reported by Deng et al in a meta-analysis (72) (31%) and Tong et al (7) (37%) among healthcare workers in the early stages of the COVID-19 pandemic in China. Compared to Lai et al's study (5) (50.4%) among healthcare workers at the peak of the pandemic in China, our study found a lower prevalence in the post-pandemic era, which may be because of the potential decreased fear and uncertainty from a better understanding of the COVID-19 and some appropriate interventions taken to relieve depressive symptoms during the pandemic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence rates of depressive and anxiety symptoms for healthcare workers in the post-pandemic era were generally comparable to those observed in previous studies during the COVID-19 pandemic era, but different from the prevalence before the pandemic. In this study, we found that the prevalence of depressive symptoms was 34.7%, which was nearly in line with that reported by Deng et al in a meta-analysis (72) (31%) and Tong et al (7) (37%) among healthcare workers in the early stages of the COVID-19 pandemic in China. Compared to Lai et al's study (5) (50.4%) among healthcare workers at the peak of the pandemic in China, our study found a lower prevalence in the post-pandemic era, which may be because of the potential decreased fear and uncertainty from a better understanding of the COVID-19 and some appropriate interventions taken to relieve depressive symptoms during the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Facing the unprecedented situation, healthcare workers have made great efforts to provide medical treatment and care to control the epidemic quickly during the COVID-19 pandemic and faced excessive workloads and psychological pressure, thereby having a large proportion of psychological problems. Compared to other occupational groups, they were particularly vulnerable to psychological problems ( 5 7 ) and more than one-third of healthcare workers experienced anxiety and depression during the COVID-19 pandemic globally ( 8 ) and in China ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, to determine the prevalence of psychological distress, we further dichotomized the KPDS into no distress and mild-to-severe distress, using a cut-off total KPDS score of < 20 and ≥ 20, respectively. 30 We also computed the prevalence of mild-toextreme fear of COVID-19 by dichotomizing scores into no fear (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and mild-to-extreme fear (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Third, multiple linear regression was performed with psychological distress as outcome and fear of COVID-19 as predictor while adjusting for sociodemographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals experienced increased workload and were required to work overtime, adhere to dynamic infection prevention policies, and deal with constant exposure to traumatic situations 6 . Previous studies have shown that the demands of the pandemic resulted in poor psychological outcomes among health professionals including increased psychological distress, burnout, depressive symptoms, anxiety, occupational stress, and posttraumatic stress disorder 7–9 . For instance, a multicenter study in Ghana reported that 21.1% and 27.8% of frontline healthcare professionals had experienced depression and anxiety respectively, 5 months into the pandemic 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation